Tacrolimus-Related Cerebral Microbleeds after Lung Transplantation - L. Mechtouff; F. Piegay; J. Traclet; F. Philit; P. Boissonnat; M. Hermier; I. Durieu; T.-H. Cho; N. Nighoghossian; J.-F. Mornex (Case Reports in Transplantation)
Posterior reversible encephalopathy syndrome is a well-known complication of treatment by tacrolimus. We report 2 cases of lung transplant recipients treated with tacrolimus who developed cerebral microbleeds on T2*-weighted sequences in the acute setting of posterior reversible encephalopathy syndrome. Cerebral microbleeds may be a marker of tacrolimus-induced vasculopathy that may be detected earlier by neuropsychological and magnetic resonance imaging monitoring in transplant recipients treated with tacrolimus.